Is There Any Difference Between Flesch Reading Ease Formula and Dale-Chall Formula? - Siti Hajar; Junaidi Mistar (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
This study discussed the difference between Flesch Reading Ease Formula and Dale-Chall Formula in analyzing the English textbook for 10th grade in Indonesia. In addition, this study also explains how the reading materials were adequate for the levels of students. This research used qualitative evaluation, which is a descriptive analysis to analyze and describe the data. The data of this research are in the form of tables taken in the readability formula. The collected data of this research were then analyzed by classifying the table of readability formula used. The result showed that found the different quality text for 10th grade in the readability index used. Affirm the research findings, and some suggestions for educators to operate the readability formulas to endow proper reading material for students. Keywords: flesch reading formula; dale-chall formula; readability